Book Reprography in Copyright - Darmanto, Nova; Delliana, Santi (International Journal Labs, 2023)
Books are evolving into one of the most important mass communication tools on the planet. As a result, buying books through manufacturing and distribution is a crucial form of mass communication. The research’s purpose is to explore book reprography in copyright. The researchers used qualitative approach with literature study as the research design. The data were generated from different literature, mainly relevant books and scientific articles. The researchers discovered that, under copyright law, the creator's exclusive right arises immediately based on the declarative principle after a work is realized in tangible form, subject to limitations in accordance with statutory and regulatory conditions.